The Value Chain Approach in One Health: Conceptual Framing and Focus on Present Applications and Challenges - Antoine-Moussiaux, Nicolas; Peyre, Marisa; Bonnet, Pascal; Bebay, Charles; Bengoumi, Mohammed; Tripodi, Astrid (Frontiers in Veterinary Science, 2017)
The value chain (VC) is a major operational concept for socio-economic analysis at meso level. Widely mobilized in development practice, it is still undergoing conceptual and practical refining, e.g. to take account of environmental and social sustainability. Briefly, VC refers to a system of value creation through the full set of actors, links, technical and commercial activities and flows involved in the provision of a good or service on a market. In the last decade, this concept has been promoted in the management of animal health. In particular, the emergence of Highly Pathogenic Avian Influenza (HPAI) has triggered an interdisciplinary dynamic including VC analysis as a central tool. These efforts promoted participatory investigation methods in the analysis of health systems. Using qualitative and quantitative data, these methods acknowledge the usefulness of actors’ involvement and knowledge, hence facilitating the transdisciplinarity needed for effective action. They fit into adaptive and action-oriented strategies, fostering stakeholders’ participation. Recent research on HPAI surveillance in South-East Asia merged VC and participatory approaches to develop innovative tools for analyzing constraints to information flow. On-going interventions for HPAI prevention and control as well as the prevention of other emerging zoonotic risks in Africa are presently building on this VC framework to develop strategies for its application at national and regional scales. Based on the latter experiences, this paper proposes a field-based perspective on VC applications to animal and public health systems, within a One Health approach responding to the overall challenge of complexity.